Pengaruh Variasi Produk dan Celebrity Endorsment Terhadap Kepuasan Konsumen yang Berdampak pada Keputusan Pembelian Produk Safi - Erika Dona Pratiwi; Herwin (UNIVERSITAS KALBIS, 2022)
This objectives of study is to know how the Effect of Product Variation and Celebrity Endorsement on Consumen Satisfaction that Impacts on Safi Product Purchasing Decisions. This research uses quantitative methods with non Probability Sampling techniques. A sample of 150 respondents were consumers who had used Safi products. The results showed that Product Variation has a significant influence on the Purchase Decision of Safi products. Likewise the Safi Product Purchase Decision has an effect on Consumer Satisfaction, while Celebrity Endorsement has no significant influence on the Safi Product Purchasing Decision.